Objective structured clinical examination: Do first-year nursing students perceive it to be stressful? - Dorothee Line Adibone Emebigwine; Ntombizodwa S.B. Linda; Penelope Martin (AOSIS, 2023)
Background: The Objective Structured Clinical Examination (OSCE) is widely accepted as an effective means of assessing clinical competence and nursing skills. There is, however, little existing knowledge on how first-year nursing students perceived stress during their first OSCE. Objectives: To determine the perception of stress; to identify the perceived factors causing stress; and to determine the perceived incidence of stress. Method: A descriptive, survey was conducted on a sample of 82 first-year nursing students using the Perceived Stress Scale (PPS). Results: The results showed that more than half (n = 54) of students perceived stress at moderate levels. Students not having sufficient time to complete the OSCE was perceived as the main factor causing stress (mean = 22.04; standard deviation [s.d.] = 6.21). The correlation between perception of stress and perceived factors causing stress showed a significant weak positive linear correlation among the variables (r = 0.45; p  0.05). Conclusion: The study findings are important as the data determining the first-year nursing students' perception of stress were collected immediately after their first OSCE, which may indicate that perception of stress was related to the actual event rather than the preparation for the OSCE. A follow-up qualitative research study should be conducted, preferably in the same setting, so that the students' experiences of stress during the first OSCE can be explored in depth.